Optimizing the Chemiluminescence of a Light-Producing Deoxyribozyme - Jakubec, Martin; Pšenáková, Karolína; Svehlova, Katerina; Curtis, Edward A (Chembiochem, 2022)
Supernova is a chemiluminescent deoxyribozyme recently discovered in our group. It transfers the phosphate group from the 1,2-dioxetane substrate CDP-Star to its 5' hydroxyl group, which triggers a decomposition reaction and the production of light. Here we investigated the effects of reaction conditions on the ability of Supernova to generate a chemiluminescent signal (using a plate reader assay) and to phosphorylate itself (using a ligation assay). Our experiments indicate that multiple zinc ions are required for catalytic function, suggesting links between Supernova and protein enzymes that catalyze similar reactions. They also show how factors such as pH, potassium concentration, CDP-Star concentration, and DNA concentration affect the reaction. By combining information from different experiments, the rate enhancement of light production was increased by more than 1000-fold. These results should be useful for applications in which Supernova is used as a sensor.
Keywords: DNA katalytická; kinetika; deoxyribozyme; Kinetics; chemiluminescence; in vitro selection; supernova; sensors; Luminescence; DNA; luminiscence; DNA, Catalytic